2001
DOI: 10.1023/a:1021107602535
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Analysis of nucleotide sugar metabolism is essential in studying glycosylation in cells. Here we describe practical methods for both extraction of nucleotide sugars from cell lysates and for their analytical separation. Solid-phase extraction cartridges containing graphitized carbon can be used for the purification of nucleotide sugars by using triethylammonium acetate buffer as a ion-pairing reagent for decreasing retention. After that they are separated by high-performance liquid chromatography using a C18 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…However, nucleotide-activated sugars are highly polar molecules and, therefore, have limited affinity toward reverse-phase sorbents such as C18 and C8, which are typically found in SPE materials. Recently, Räbinä et al (22) reported impressive recoveries of sugar-nucleotides from yeast and bacterial cells using graphitized non-porous carbon SPE material along with the ion-pairing reagent, triethylammonium acetate, in the elution solvent. Subsequent ion-pairing LC experiments permitted separation of intracellular sugarnucleotides, and their identification was possible by matrix-assisted laser desorption ionization time-of-flight MS (22).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, nucleotide-activated sugars are highly polar molecules and, therefore, have limited affinity toward reverse-phase sorbents such as C18 and C8, which are typically found in SPE materials. Recently, Räbinä et al (22) reported impressive recoveries of sugar-nucleotides from yeast and bacterial cells using graphitized non-porous carbon SPE material along with the ion-pairing reagent, triethylammonium acetate, in the elution solvent. Subsequent ion-pairing LC experiments permitted separation of intracellular sugarnucleotides, and their identification was possible by matrix-assisted laser desorption ionization time-of-flight MS (22).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Räbinä et al (22) reported impressive recoveries of sugar-nucleotides from yeast and bacterial cells using graphitized non-porous carbon SPE material along with the ion-pairing reagent, triethylammonium acetate, in the elution solvent. Subsequent ion-pairing LC experiments permitted separation of intracellular sugarnucleotides, and their identification was possible by matrix-assisted laser desorption ionization time-of-flight MS (22). Using commercially available ENVI-Carb SPE cartridges, intracellular sugar-nucleotides were extracted from the cell lysates of C. jejuni 81-176 and the isogenic mutant pseC using an optimized SPE method based on that of Räbinä et al (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ion-exchange chromatography and reversed phase liquid chromatography has been used for the determination of nucleotide sugars [20][21][22][23][24]. Ion-pairing chromatography [25,26] coupled with mass spectrometry and nuclear magnetic resonance [27] has likewise been applied to the determination of nucleotide sugars. CE has also been used for the separation and determination of nucleotide sugars in two reports [28,29] with promising results.…”
Section: Introductionmentioning
confidence: 99%